Healthcare educators’ perspectives on IPE implementation at a Saudi university: a qualitative study - Aladwani, Mohra (Frontiers in Medicine, 2026)
BackgroundInterprofessional education is one of the pedagogies recommended to help enhance the knowledge and skills of future healthcare workers. Educators are important stakeholders in IPE implementation. This study aimed to explore educators’ views on IPE implementation at Taif University.MethodsHealthcare educators and leaders at the university participated in a qualitative study conducted between October 2024 and February 2025. Semi-structured interviews were conducted via Zoom. Data collection and analysis were guided by the SWOC framework (strengths, weaknesses, opportunities, and challenges). Thematic analysis was conducted to analyze the data.ResultsA total of 21 educators from healthcare programs participated in the study. Educators with prior exposure to IPE, the location of some of the colleges, and the presence of a simulation center were perceived as strengths. Opportunities were identified in improving students’ attitudes and skills within a collaborative work environment, and in enhancing collaboration with staff from various programs and clinicians from hospitals. Logistical barriers, staff resistance, bureaucratic approval processes, hierarchies, and lack of a university hospital were perceived as weaknesses and challenges that might hinder implementation efforts.ConclusionThis exploratory study provides insights into the views of educators and leaders about IPE implementation at Taif University. The overwhelming majority of participants had positive views on IPE integration into healthcare programs. Educators with prior exposure to IPE can advocate for IPE and help raise awareness of IPE among university staff and students. Decision-makers involved in implementing IPE can use these findings and make efforts to address the challenges and weaknesses identified.